Impact of Green Energy Production, Green Innovation, Financial Development on Environment Quality: A Role of Country Governance in Pakistan - Bhutta, Aamir Inam; Ullah, Muhammad Rizwan; Sultan, Jahanzaib; Riaz, Ahsan; Sheikh, Muhammad Fayyaz (International Journal of Energy Economics and Policy, 2022)
The study aims to analyze the contributions of green innovation, green energy production, and financial development to environmental quality with the moderating role of country governance. The study collects data from a panel of five South Asian economies from 2000 to 2018. The paper includes CIPS, a second-generation unit root to test the data's stationarity, and the Westerlund co-integration to investigate the long-term relationship between determinants. The Fully Modified and Dynamic Ordinary Least Square is applied to estimate the long-run coefficient and test the hypothesized relationship between selected determinants. The study finds that green innovation and green energy production negatively (positively) contribute to environmental degradation (environment sustainability). Moreover, financial development has a substantial impact on environmental degradation and sustainability, as per the findings. The study further finds a significant role of country governance in the relationship between green innovation, green energy production, environmental degradation, and environmental sustainability. Furthermore, country governance is improving the link between financial development and environmental degradation, and long-term sustainability.